THE RELATION BETWEEN PUBLIC DEBT AND GDP - EMPIRICAL ANALYSIS FOR MACEDONIA AND ROMANIA - Nina Kyoseva (Acta Scientiarum Polonorum. Oeconomia, 2016)
The financial crises in 2008 initiated a broad debate on the challenges posed to the economic growth and development by crossing a specific threshold in the ratio between the public debt and the GDP, so that it can be sustainable and without harmful consequences on the future development perspectives. In this paper analysis of comparative data for Macedonia and Romania is performed, having in mind the following facts: both countries belonged to the former socialist block of countries; both countries went through very painful process of socio-economic transition; and Romania is an EU member-country since 2007 and is a good example for Macedonia for its future macroeconomic policies, once it becomes the EU member country in near future. The initial assumption in the research is that there is long run causality between public debt and GDP, as well as short run inverse relationship between the growth rates of these variables. Therefore, cointegration test for the data for Romania is conducted and then vector error correction model (VECM) is applied.